2015
DOI: 10.1016/j.cmet.2015.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Identification of AMPK Phosphorylation Sites Reveals a Network of Proteins Involved in Cell Invasion and Facilitates Large-Scale Substrate Prediction

Abstract: Summary AMP-activated protein kinase (AMPK) is a central energy gauge that regulates metabolism and has been increasingly involved in non-metabolic processes and diseases. However, AMPK's direct substrates in non-metabolic contexts are largely unknown. To better understand the AMPK network, we use a chemical genetics screen coupled to a peptide capture approach in whole cells, resulting in identification of direct AMPK phosphorylation sites. Interestingly, the high-confidence AMPK substrates contain many prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
135
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(146 citation statements)
references
References 63 publications
(116 reference statements)
11
135
0
Order By: Relevance
“…(Datasets S1-S4). Thus, although Western detection of thiophosphorylation is a useful tool, it is limited in comparison with MS results as observed in this study and others (20).…”
Section: Resultsmentioning
confidence: 84%
“…(Datasets S1-S4). Thus, although Western detection of thiophosphorylation is a useful tool, it is limited in comparison with MS results as observed in this study and others (20).…”
Section: Resultsmentioning
confidence: 84%
“…We found evidence that metformin enhanced AUF1 binding to HSP70 and increased HSP70 localization in the nucleus. Interestingly, a ~70 kDa band that was serine–threonine‐phosphorylated in AUF1 immunoprecipitates might represent HSP70, recently identified as a substrate of AMPK (Schaffer et al ., 2015). It has been observed that phosphorylation of AUF1 has been reported to regulate AUF1 protein stability and binding to target mRNAs (Wilson et al ., 2003; Li et al ., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to a pivotal regulatory function in metabolism, AMPK has been recently shown to modulate cell invasion [49]. Cell invasion is an energy consuming process, thus FA oxidation should play an important role in the regulation of trophoblast invasion due to its high efficiency in ATP production.…”
Section: Discussionmentioning
confidence: 99%